Separation of cell survival, growth, migration, and mesenchymal transdifferentiation effects of fibroblast secretome on tumor cells of head and neck squamous cell carcinoma - Veronika Maria Metzler; Christian Pritz; Anna Riml; Angela Romani; Raphaela Tuertscher; Teresa Steinbichler; Daniel Dejaco; Herbert Riechelmann; József Dudás (Tumor Biology, 2017)
Fibroblasts play a central role in tumor invasion, recurrence, and metastasis in head and neck squamous cell carcinoma. The aim of this study was to investigate the influence of tumor cell self-produced factors and paracrine fibroblast–secreted factors in comparison to indirect co-culture on cancer cell survival, growth, migration, and epithelial–mesenchymal transition using the cell lines SCC-25 and human gingival fibroblasts. Thereby, we particularly focused on the participation of the fibroblast-secreted transforming growth factor beta-1.Tumor cell self-produced factors were sufficient to ensure tumor cell survival and basic cell growth, but fibroblast-secreted paracrine factors significantly increased cell proliferation, migration, and epithelial–mesenchymal transition–related phenotype changes in tumor cells. Transforming growth factor beta-1 generated individually migrating disseminating tumor cell groups or single cells separated from the tumor cell nest, which were characterized by reduced E-cadherin expression. At the same time, transforming growth factor beta-1 inhibited tumor cell proliferation under serum-starved conditions. Neutralizing transforming growth factor beta antibody reduced the cell migration support of fibroblast-conditioned medium. Transforming growth factor beta-1 as a single factor was sufficient for generation of disseminating tumor cells from epithelial tumor cell nests, while other fibroblast paracrine factors supported tumor nest outgrowth. Different fibroblast-released factors might support tumor cell proliferation and invasion, as two separate effects.